Between alternative and traditional social platforms: the case of gab in exploring the narratives on the pandemic and vaccines - Acampa, Suania; Crescentini, Noemi; Padricelli, Giuseppe Michele (Frontiers in Sociology, 2023)
The phenomenon of deplatforming (Rogers, 2020;Innes and Innes, 2021;Jhaver et al., 2021) intended as the removal of social media accounts because of breaking rules on mainstream platforms such as Facebook, Twitter, YouTube and Instagram, recently increased due to new terms and conditions of use of digital media new alternative social media platforms emerged and presented itself as protectors of freedom expression. In this way, it becomes interesting to understand better the context of these platforms, so-called web suburbs that consists in those digital places that «host what we can generally call "subcultures," including fandoms, religious sects, political extremists and, subcultures» (Thibault, 2016: 390) The alternative social media platforms are intended as all those connection services between users halfway between a social media and a discussion forum born to boycott the censorship actions of the main social media platforms (Meta Group, Twitter, etc.) and celebrate free speech (Donovan et al., 2019;Fair and Wesslen, 2019;Jasser et al., 2021) even on controversial positions. How are sensitive topics, such as the one that concerns the scepticism related to the approvals of vaccines during the pandemic, addressed on the alternative social media platform compared to how they are dealt with on the mainstream social media platform?This explorative work wonders about the users' points of view on vaccine concerns and the relevant differences between Gab and Facebook in addressing this topic. The collection procedure considered the different platform's structure and their different organization of the interaction spaces. Our work's methodological output deals with comparing these social media platforms, bearing in mind their ontological objects and their algorithms' role. Through the Content Analysis techniques, we underline the differences and similarities of the platforms in terms of the type of content posted, engagement rates and information source reliability. In addition to the type of communication and information circulating on a powerful platform such as Gab, the results help us understand the different narratives promoted on the two social media platforms and their role in the possible promotion of same sentiment, opinions and ideological polarization.